Hikayat Desa Isyarat: learning language of the impaired using game-based approach - Abdullah, Amirah Izzati; Ahmad Fesol, Siti Feirusz (College of Computing, Informatics, and Mathematics, 2025)
Malaysian Sign Language (MSL), a topic unfamiliar to many, have been around since the 1960s. Some that are familiar chose to not delve into it as it seems difficult, time-consuming, and boring, while others, a small percent of eager learners, work-life constraints sadly further hinder their learning process. In order to remediate these ongoing issues, a fun yet engaging educational approach is needed— game-based learning (GBL). As one of the ever-evolving educational tools, GBL will surely pique the public’s interest in MSL by making learning enjoyable. As games are basically an integral part of everyday life for the majority of people these days, a mobile 2D GBL approach promises accessibility and engagement. This project highlights on designing an interactive MSL learning game as well as evaluating its usability, enjoyment, and effectiveness. The Game Development Life Cycle (GDLC) is adopted for the smooth and organized progression of this project. Upon completion, 20 random respondents assessed the game in accordance to the E-Game Flow Model, resulting to quite a fruitful 80.5% enjoyment level, thus proving this effective educational approach. This project serves as an extensive guide for future educators or developers looking to promote MSL through GBL in a way that enhances one’s engagement, understanding, and accessibility, while highlighting areas for future improvements and broader applications.